2021
DOI: 10.3390/plants10010154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression of Four Aquaporin Genes in Impatiens walleriana during Drought Stress and Recovery

Abstract: Aquaporins comprise a large group of transmembrane proteins responsible for water transport, which is crucial for plant survival under stress conditions. Despite the vital role of aquaporins, nothing is known about this protein family in Impatiens walleriana, a commercially important horticultural plant, which is sensitive to drought stress. In the present study, attention is given to the molecular characterization of aquaporins in I. walleriana and their expression during drought stress and recovery. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Furthermore, the color of flowers of some populations displays a significant variability and instability within intraspecies in these Impatiens taxa. For example, in the previous literature [ 7 ], lateral sepals of Impatiens platychlaena are purple, but in this study, the color changes gradually, ranging from purple, yellow with purple spots to pure yellow, based on years of field observation ( Figure 8 Dd–Gg). Similarly, the flower of Impatiens toxophora is multicolor with the flower color varying from white, yellow to purple within the same population ( Figure 8 Hh–Ll).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Furthermore, the color of flowers of some populations displays a significant variability and instability within intraspecies in these Impatiens taxa. For example, in the previous literature [ 7 ], lateral sepals of Impatiens platychlaena are purple, but in this study, the color changes gradually, ranging from purple, yellow with purple spots to pure yellow, based on years of field observation ( Figure 8 Dd–Gg). Similarly, the flower of Impatiens toxophora is multicolor with the flower color varying from white, yellow to purple within the same population ( Figure 8 Hh–Ll).…”
Section: Discussionmentioning
confidence: 50%
“…Impatiens species occur in diverse habitats, such as in forest understories, roadside ditches, valleys, abandoned fields, along streams and in seepages, usually in mesic or wet conditions, although some species can tolerate drier habitats [6]. Due to their beautiful appearance and long flowering period, many species of Impatiens are grown all over the world as ornamental plants [7]. Many new species of Impatiens have been discovered and described in recent years [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For qRT-PCR, the following thermal cycling conditions were used: initial denaturation at 95 • C, followed by 40 cycles of denaturation at 95 • C for 30 s, annealing at 60 • C for 30 s, and extension at 72 • C for 30 s. Each sample underwent qRT-PCR in triplicate. Primer sequences and their accession numbers have been described previously in the works of Ðurić et al [35,73].…”
Section: Analysis Of Aquaporin and Aba Metabolic Gene Expressionmentioning
confidence: 99%
“…Aquaporins form channels in cell membranes and can transport various molecules through them, with water channel function being the best described [34]. Aquaporin expression was affected by drought in Impatiens walleriana [35] and by MeJA foliar application in Setaria italica [36]. However, it is not well understood how jasmonates affects the expression of aquaporins in different plant species under drought or other abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaporins are water channel proteins that facilitate the passage of water through cell membranes and are important in drought tolerance of plants [9]. Reuscher and his team identified 47 aquaporin genes in the tomato genome and found that they are expressed in a tissue-specific manner.…”
Section: Aquaporin Genesmentioning
confidence: 99%